Synovial doppler ultrasonography and dynamic magnetic resonance imaging of the hand and wrist in the assessment of early inflammatory arthritis versus rheumatoid arthritis : contribution for a new prediction model - NAVALHO, MÁRCIO (2013)
Tese de doutoramento, Medicina (Imagiologia), Universidade de Lisboa, Faculdade de Medicina, 2012